Pengaruh Pola Komunikasi Organisasi Terhadap Kinerja Anggota BEMP IKOM Universitas Negeri Jakarta Periode 2024/2025 - Basyaasyah Auladdina Islami; Maulina Larasati Putri; Muhammad Fikri Akbar (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2026)
The fellow members of the organization must coordinate with each other and workztogether tozachieve thehgoals of the organization. Good communication from each member will definitely make the implementation of the organization run well, and vice versa. Activities that occur in the organization are supported by organizational communication, In organizational communication there are three sides of view that are of course different, namely communication from superiors to subordinates, communication between members and the last is communication that comes from members to their superiors and it can be seen from each point of view that communication has its own pattern. The delivery of messages or information from these patterns is known to affect the performance or work results of members in the organization. Therefore, the purpose of this study is specifically to find out and prove howzthe influencezof organizational comunication patterns on the performance of BEMP IKOM UNJ members for the 2024/2025 period. The research methodology is quantitative and uses a data collection method with a survey type. The results show that the independent variable in this study, namely organizational communication patterns, affects the dependent variable, namely member performance. It is known that the variable of organizational communication patterns has an effect of 31% on member performance. Then it can also be concludedzthat the influence of several variables that were not tested and then inserted into the form of this study was 69%.